Direct medical costs of complications of diabetes in the United States: estimates for event-year and annual state costs (USD 2012). (March 2014) - Ward, Alex; Alvarez, Piedad; Vo, Lien; Martin, Silas
Abstract Objective: To estimate the direct medical costs associated with managing complications, hypoglycemia episodes, and infections associated with type 2 diabetes expressed in 2012 United States dollars (USD). Methods: Direct data analysis and microcosting were used to estimate the costs for an event leading to either a hospital admission or outpatient care, and the post-acute care associated with managing macrovascular and microvascular complications, hypoglycemia episodes, and infections. Data were obtained from many sources, including inpatient and emergency department databases, national physician and laboratory fee schedules, government reports, and literature. Event-year costs reflect the resource use during an acute care episode (initial management in an inpatient or outpatient setting) and any subsequent care provided in the first year. State costs reflect annual resource use required beyond the first year for the ongoing management of complications and other conditions. Costs were assessed from the perspective of a comprehensive US healthcare payer and expressed in 2012 USD. Results: Event-year costs (and state costs) for macrovascular complications were as follows: myocardial infarction 56, 445 (1904); ischemic stroke 42, 119 (15, 541); congestive heart failure 23, 758 (1904); ischemic heart disease 21, 406 (1904); and transient ischemic attack 7388 (179). For two microvascular complications the event-year and state costs were assumed the same: 71, 714 for end stage renal disease, and 2862 blindness. The event-year cost was 9041 for lower extremity amputations, and 2147 for diabetic foot ulcers. Costs were also determined for managing hypoglycemic episodes: 176–16, 478 (depending on treatment required), and infections: vulvovaginal candidiasis 111, lower urinary tract infection 105. Conclusions: This study, which provides up-to-date cost estimates per patient, found that managing macrovascular and microvascular complications results in substantial costs to the healthcare system. This study facilitates conduct of other research studies such as modeling the management of diabetes and estimating the economic burden associated with complications.